Feito para nós? : autoconceito em contraponto à imagem idealizada das mães na propaganda - Merege, Verônica Cristina Cardoso (2020)
This dissertation has as its central theme the construction of the social identity of the Brazilian mother, discussing her self-concept as a counterpoint to the stereotyped representation of motherhood in advertising. The theoretical basis has its copyright in the Theory of Social Identity (TIS), including the defined self-concept Tajfel (1984), associated with a literature review on gender representation, and the most critical of women in advertising and its articulations based on stereotypes. In the spectrum of diverse realities, mothers are forged to escape from a single pattern. The so-called plural mothers, who do not identify with traditional mothers, already represent almost 1.1 million Brazilian women (IBGE, 2017). Supported by the phenomenological qualitative method, this research presents presentations and meanings of motherhood and advertising explored in depth with 6 women living in São Paulo, culminating in 4 hours of recording and 39 pages of transcription. The results show that both mothers and traditionals do not identify with conventional advertising and both move to see their own struggles as mothers in the advertisement that seeks mothers as plurals. The effect of stereotyped representations of the traditional mother on advertising is not positive for the group of mothers, regardless of their self-concept, to permeate between traditional or plural representations. The negative effect of stereotypes is due to the negative connotation applicable to female subordination oriented to accommodate the interests of the family, repressing their demands and reinforcing the role of full responsibility for women, contributing to a monolithic view of identity. This research contributes to a discussion on the gender of women, present in the literature on TIS, which refers to the role of propaganda in the construction of stereotypes of mothers, little explored in the most recent literature in Brazil. Additionally, it brings insights for advertisers, brand managers and marketing professionals in the construction of advertising campaigns that are more assertive in their discursive as well as imaginary content, allowing them to receive a wide and heterogeneous audience of mothers, when considering the elements that are as expensive as the others. plural mothers, as well as betting on their differences, segmenting an advertisement.